Causes and Expectations: On the Interpretation of the Tagalog Ability/Involuntary Action Form. (14th July 2021) - Alonso-Ovalle, Luis; Hsieh, Henrison
Abstract: The Tagalog Ability/Involuntary Action (aia ) verbal form conveys apparently unrelated modal meanings: that an action was within what an agent could do or that it was beyond what an agent could control, for instance. Recent analyses for the Malagasy and St'át'imcets counterparts of this form propose that this morphology contributes circumstantial modality and conveys, roughly, that the event described follows from a set of facts ( Davis et al., 2009 ; Paul et al., 2016 ). We discuss some challenges for extending this type of analysis to Tagalog and present an alternative proposal. We follow previous analyses in assuming that the aia form projects its domain of possibilities from a set of facts, but depart from these analyses by proposing (i) that the modal component of the Tagalog aia form is non-at-issue and (ii) that it conveys, via a presupposition, that this event was not expected given the facts that the described event is taken to causally depend on.